TUBERKULOMA SEREBRAL PADA PENDERITA ACQUIRED IMMUNE DEFICIENCY SYNDROME - Vincent Ongko Wijaya; Dony Ardianto; Gama Sita Setya Pratiwi; Anton Mahendra; Glennis Widra Shintyalola; Rasi Irfan Asany (PERDOSNI, 2020)
Cerebral tuberculoma is a central nervous system complication which rare and jeopardize due to tuberculosis (TB) infection. The authors reports a case of a 23 years old female with history of human immunodeficiency virus infection and acquired immunodeficiency syndrome (HIV/AIDS) and under treatment for active TB, presented with headache and dizziness since 1 week before admission. Neurological examination in normal range. Lab value showed decrease level in CD4 absolute and continue with contrast head CT scan. The patient has been given main therapy with dexamethasone, cotrimoxazole, and anti-tuberculosis drugs Keywords: HIV/AIDS, tuberculoma, tuberculosis